Semi-Essentially Compressible Modules and Semi-Essentially Retractable Modules - Al Hakeem, Mohammed Baqer Hashim; Al-Mothafar, Nuhad Salim (Iraqi Journal of Science, 2023)
Let be a commutative ring with 1 and be a left unitary . In this paper, the generalizations for the notions of compressible module and retractable module are given. An is termed to be semi-essentially compressible if can be embedded in every of a non-zero semi-essential submodules. An is termed a semi-essentially retractable module, if for every non-zero semi-essentially submodule of an . Some of their advantages characterizations and examples are given. We also study the relation between these classes and some other classes of modules.